2014
DOI: 10.1155/2014/145342
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester and Therapeutic Potentials

Abstract: Caffeic acid phenethyl ester (CAPE) is a bioactive compound of propolis extract. The literature search elaborates that CAPE possesses antimicrobial, antioxidant, anti-inflammatory, and cytotoxic properties. The principal objective of this review article is to sum up and critically assess the existing data about therapeutic effects of CAPE in different disorders. The findings elaborate that CAPE is a versatile therapeutically active polyphenol and an effective adjuvant of chemotherapy for enhancing therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 116 publications
2
136
0
5
Order By: Relevance
“…CAPE is a natural bioactive compound which has various pharmacological and biological activities such as antioxidant, anticancer, anti-inflammatory, antiviral, anti-metastatic, immunomodulatory, antiplatelet and antilipidemic eff ect 21,18,19,15,16,20,39) An animal study revealed that high serum levels of low-density lipoprotein cholesterol (LDL-C) was significantly associated with the incidence of ONFH 40) . In another study total serum cholesterol and triglyceride levels were found signifi cantly higher in animals with ONFH compared to controls 35) .…”
Section: Pt Aptt and Inr Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CAPE is a natural bioactive compound which has various pharmacological and biological activities such as antioxidant, anticancer, anti-inflammatory, antiviral, anti-metastatic, immunomodulatory, antiplatelet and antilipidemic eff ect 21,18,19,15,16,20,39) An animal study revealed that high serum levels of low-density lipoprotein cholesterol (LDL-C) was significantly associated with the incidence of ONFH 40) . In another study total serum cholesterol and triglyceride levels were found signifi cantly higher in animals with ONFH compared to controls 35) .…”
Section: Pt Aptt and Inr Resultsmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) is an important component derived from propolis, a component of beehive 15) . There are more than 300 substances in propolis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons given by TCM doctors were poor quality of current medicinal materials accounting for 89.04 % , inappropriate methods of decocting and taking medicine for 47.84 %, and decreased ability to make a correct syndrome differentiation for 35.88 %. Besides, unawareness of the stipulated dose of the corresponding herbs in pharmacopeia by most of TCM doctors [8] and actuation of economic profit also need take into consideration. Meanwhile, the flexibility and arbitrariness of Chinese herbs in dosage by TCM doctors were reflected from the values of standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) is one of active components of propolis that is a honey bee product [10]. Traditional medicine takes advantage of propolis as a dietary supplement for therapeutic aims.…”
Section: Introductionmentioning
confidence: 99%